Musyrifah Strategies for Addressing Homesickness Among Female Students in An Indonesian Islamic Boarding School - Khoridatul Bahiyah; Muhammad Husni (AL-ISHLAH: Jurnal Pendidikan, 2026)
Homesickness is a common psychosocial challenge among students transitioning to residential education, potentially hindering emotional adjustment and social adaptation. Although previous studies have examined homesickness as an individual psychological condition, limited attention has been given to the role of resident mentors (musyrifah) in supporting students within Islamic boarding schools (pesantren). This study explores the dynamics of homesickness and the mentoring strategies employed by musyrifah to facilitate students' adaptation.A qualitative case study was conducted at Al-Khoirot Islamic Boarding School for Girls, Malang, Indonesia. Six participants, comprising three musyrifah, two newly admitted female students experiencing homesickness, and one guidance and counseling teacher, were purposively selected. Data were collected through semi-structured interviews, non-participant observation, and documentation, and analyzed using Miles and Huberman’s interactive thematic analysis.Homesickness was manifested through emotional longing, cognitive rumination, social withdrawal, and adaptation difficulties. The findings indicate that musyrifah supported students through continuous emotional monitoring, relational mentoring, intensive individual assistance, structured activity engagement, and collaboration with guidance and counseling teachers. These interconnected strategies fostered emotional security, strengthened social connectedness, and facilitated gradual adjustment to boarding school life.The findings highlight the central role of musyrifah as first-line emotional supporters in managing homesickness through sustained relational mentoring embedded in students’ daily lives. This study contributes a contextual understanding of institution-based emotional support in Islamic boarding schools while underscoring the need for broader multi-site studies to examine the transferability of these findings.